Electroencephalography in Determining Mood in Animals (London Journal of Engineering Research, 2023)
Electroencephalography is one of the most common methods used in the interpretation of neurological activities in the brain of humans and various model animals. With the electroencephalography method, it is possible to obtain information about the various changes that occur in the model creature, its relationship between species, and its emotional state. It is observed that various behaviors are exhibited in model animals due to some factors such as mood, sleep disorder, epilepsy, depression, pain, drug use, addiction, genetics, and environmental. When these behaviors are examined in the studies; neurodevelopmental disorders, mood disorders, olfactory disorders, visual attention dysfunction, sleep disorders, brain dysfunction, learning disorder, various adjustment, autistic-like behavioral disorders, autism, attention deficit, hyperactivity, anxiety, aging, traumatic brain injury, repetitive grooming It has been observed to cause various behaviors such as social deficits, decreased activity, anxiety, fear conditioning, calmness, staring, anxiety, fear, learning disability, intermodal recognition memory, and depression. The results of the studies show that these behaviors are closely similar to electroencephalographic humans and various model animals. This study, it is aimed to give information about the state of hearing between humans and various model animals with the method of electroencephalography.
Keywords: behavior; model animal; neuroscience; mood; electroencephalography